Perception Of Second Year Medical Students On Using Standardized Patients For Learning Communication Skills At The School Of Medical Sciences, Universiti Sains Malaysia: A Developmental Project - Sepehr, Shima (2011)
Standardized Patients (SPs) has been used as an educational tool for clinical teaching and learning skills among medical students in developed countries. It refers to individuals who have been carefully trained and skilled to take on the characteristics of real patients. Using SPs is one way to minimize if not prevent. unnecessary risks in dealing with real patients in the process of learning and competency development. Since the establishment of the School of Medical Sciences, Universiti Sains Malaysia in 1979, SPs has not been introduced to the medical students. The objective of the study was to look at the second year medical students’ perception toward SPs for learning to communicate with patients during history taking.The study comprised of two components: a developmental project and a descriptive research component. The purpose of the first part of the study was to develop a script and then used it to train Standardized Patients (SPs). We trained 6 SPs but used 4 SPs with the remaining as 2 SPs substitutes and used the for teaching learning session. Second part of the study was a descriptive research study that utilised a five-point Likert scale questionnaire to obtain the second year medical students’ perception regarding the use of SPs. It was conducted at the School of Medical Sciences, Universiti Sains Malaysia during the teaching of the Respiratory Block involving 203 medical students. Six SPs were recruited from the hospital non-clinical